Sosialisasi Raharja Information System Karyawan Absensi (RISKA) Menggunakan Metode IAC - Syafnidawati, Syafnidawati; Romansyah, Pipin; Rositawati, Devi (UNIVERSITAS RAHARJA, 2021)
Raharja Employee Attendance Information System (RISKA) is one of the existing system models at Raharja University, designed to improve the quality of information services for leaders and financial divisions regarding attendance, discipline and payroll of Raharja employees, as well as data documentation for the Human Resources Development (HRD) division. . Many previous studies have been carried out regarding employee attendance, some of which use the fingers print method and scan QR codes for employee attendance systems. This research was built with different methods in designing employee attendance models, namely by using the modified Intelligent Access Card (IAC) method. Model design is done through analysis, design, constructions and testing implementation. The test results show that the attendance of RISKA employees made in this study can make it easier for the Human Resources Development (HRD) division to provide digital information with good data validation and simplify the process of documenting manual attendance data in the form of a paper form provided by HRD then filled in by the employees in doing presence into the System.